2020
DOI: 10.2147/tcrm.s227880
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tildrakizumab: An Evidence-Based Review of Its Use in the Treatment of Moderate-to-Severe Chronic Plaque Psoriasis</p>

Abstract: Psoriasis is a common immune-mediated chronic inflammatory disease, and observations have pointed toward the IL-23/Th17 cell axis as having a key role in the pathogenesis of psoriasis. This new immunological understanding of the pathogenesis has been translated into targeted and highly effective biologic therapies. Tildrakizumab is a humanized IgG1/k monoclonal antibody targeting the p19 unit of IL-23 and has been registered for the treatment of patients with moderate-to-severe chronic plaque psoriasis in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…The EMA label also accepts dosage with 200 mg in patients with high disease burden or body weight ≥90 kg; however, this dosage is not approved anywhere else in the world. 6 Previous studies demonstrated higher efficacy of tildrakizumab in plaque psoriasis clearance as measured by PASI 75 and PASI 90 compared with the tumor necrosis factor inhibitor etanercept. 7,8 Tildrakizumab has also been shown to be well tolerated, with minimal risk of serious adverse events.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The EMA label also accepts dosage with 200 mg in patients with high disease burden or body weight ≥90 kg; however, this dosage is not approved anywhere else in the world. 6 Previous studies demonstrated higher efficacy of tildrakizumab in plaque psoriasis clearance as measured by PASI 75 and PASI 90 compared with the tumor necrosis factor inhibitor etanercept. 7,8 Tildrakizumab has also been shown to be well tolerated, with minimal risk of serious adverse events.…”
Section: Introductionmentioning
confidence: 97%
“…The EMA label also accepts dosage with 200 mg in patients with high disease burden or body weight ≥90 kg; however, this dosage is not approved anywhere else in the world. 6…”
Section: Introductionmentioning
confidence: 99%
“…Currently, as pointed out by a systematic review, positive responses have been described in cases treated by different classes of biologics, from anti‐TNF‐α to anti‐IL23. 3 , 4 Up until now, no case describing EP successfully treated by the latest anti‐IL23 approved in Europe, 5 Tildrakizumab, has been described. Here we firstly report a case of a 61‐year old man with EP successfully and safely treated by Tildrakizumab.…”
Section: Figurementioning
confidence: 99%
“…At present, the differences between the clinical benefits of inhibition of IL-17 and IL-23 remain unclear, although inhibition of IL-23 might have a broader range of effects compared to IL-17 inhibition, such as the potential clinical impact of inhibition of the production of IL-22. Regarding sustained response over time, it is tempting to speculate that the favorable long-term results with tildrakizumab may possibly be related to its inhibition of IL-23, which acts upstream in the IL-23/Th17 pathway, and as a consequence may be less prone to the triggering of collateral pathways which could favor the loss of response over time [49]. The possibility that anti-IL-23 agents are associated with more durable responses compared to agents acting on other more downstream pathways is interesting and warrants further investigation.…”
Section: Expert Opinionmentioning
confidence: 99%